Macro interventions and their influence on individual and community well-being. (November 2018) - Ferguson, Kristin M; Teixeira, Samantha; Wernick, Laura J; Burghardt, Steve
Summary: Due to the focus of micro-practice interventions on clinical outcomes and macro-practice interventions on structural outcomes, limited research exists on the clinical benefits resulting from clients' involvement in macro therapeutic interventions (i.e. structural interventions that target community, organizational, systems, and/or policy-level change and which also have clinical benefits to clients or consumers). In response to this knowledge gap, the authors present four case studies of macro therapeutic interventions in the areas of social enterprise creation, community-based participatory research, transformative organizing, and community-based partnerships. Findings: Collectively, these interventions draw from community, economic, and social development theory, empowerment theory, feminist theory, and critical theory. The authors synthesize the key intervention components across case studies that contribute to clinical and collective empowerment outcomes. Applications: The authors then offer recommendations to the social work profession for developing, implementing, and evaluating macro therapeutic interventions within clinical practice settings.